Gender in Literature: Crossing the Lines of Individuals in a Philippine Fiction - Mildred M. Crisostomo; Mark Joseph B. Layug (Research Synergy Foundation, 2021)
Under Gender Criticism, the researchers analysed Carlos Bulosan’s My Father Goes to Court to unveil the biases, stereotypes, issues, and tendencies as regard gender through the roles played by the characters in the story. Results show that on the surface, the male characters portrayed their roles based on what the society and culture accorded or dictated to them as authoritative, powerful, and dominant. Similarly, female characters were projected as powerless, weak, affective, and secondary to men. However, consciously or unconsciously, both characters crossed the borders and the lines of each other by performing roles not expected of them. On the one hand, male characters growled down to others, laughed their hearts out, and were protected. Then, on the other hand, female characters exercised power, showed leadership, manifested decision-making skills, and served as protectors. The researchers further revealed that gender is not a role to be played but an activity to be complete to avoid setting limits to any person’s tendencies. A study using the same literary text is recommended to continue its afterlife.